Alteration of wetland resilience for the intermittently and permanently inundated wetland - Jianfei Wu; Qiang Liu; Liqiao Liang; Shuzhen Li; Luoyang Gan; Haitao Wu (Environmental Research Letters)
Wetlands are influenced by the alteration of hydrological regimes induced by climate change and anthropogenic activity, affecting their structure and function. The resilience of wetlands under different hydrological status remains uncertain, which will bring risk to wetlands. To help understand the changes, this study employed the Normalized Difference Vegetation Index and early warning indicators to quantify wetland resilience across different climatic zones and compared the resilience of intermittently and permanently inundated wetlands. Furthermore, the shift of wetland resilience were explained using related meteorological variables. The results showed: ( i ) wetland resilience, theoretical recovery rates validated by empirical recovery rates, showed greater reliability in lag-one autocorrelation calculations (theoretical method), which were used to simulate wetland resilience across Northeast China; ( ii ) wetland resilience showed obvious geographical distribution trends along the climate regimes, which increased from arid to humid regimes; ( iii ) resilience of permanently inundated wetland was significantly higher than that of intermittently inundated wetland under the same climate regimes, indicating hydrological regimes play a vital role in affecting wetland integrity; and ( iv ) alteration of wetland resilience were explained by assuming that water, energy, and air temperature control wetland integrity. That is to say, that factors such as air temperature and radiation interact with hydrological regimes to affect wetland habitats. The alteration of wetland resilience brings new insight into wetland response to exogenous disturbances and the capacity for self-sustained stabilization, which will help address the impacts of climate change and anthropogenic activities.